Ultrafast cleaning of methylene blue contaminated water accelarating photocatalytic reaction rate of the BiVO4 nanoflakes under highly intense sunlight irradiation - Roy, Joy Sankar [UNESP]; Morency, Steeve; Messaddeq, Younès [UNESP] (Elsevier, 2021)
The sustainable rapid wastewater treatment process is the greatest challenge in the 21st century as the demand of fresh and clean water is increasing with growing population worldwide. Herein, an emergent technique to clean dye contaminated wastewater using sunlight is reported. The highly efficient sunlight driven photocatalyst BiVO4 nanoflakes with optical band gap of 2.63 eV have been prepared by cost-effective hydrothermal method and the photocatalytic methylene blue (MB) degradation activity of BiVO4 nanoflakes has been enhanced accelarating the photocatalytic reaction rate. The BiVO4 nanoflakes can degrade 88.86 % of methylene blue within 60 minutes for 300 mW/cm2 sunlight irradiation, whereas only 32.30 % degradation occurs for ordinary sunlight (74 mW/cm2) irradiation. The MB degradation occurs faster due to increase of photocatalytic reaction rate to 0.033 min−1 from 0.006 min−1 for tuning sunlight irradiation intensity to 300 mW/cm2 from 74 mW/cm2. This technique will open new technological opportunity for ultrafast cleaning of dye contaminated wastewater using sunlight.
Keywords: BiVO4; Methylene blue; Photocatalysis; Wastewater; Water purification